Angiotensin II type 1 receptor gene polymorphism could influence renoprotective response to losartan treatment in type 1 diabetic patients with high urinary albumin excretion rate - Dragović Tamara; Ajdinović Boris; Hrvačević Rajko; Ilić Vesna; Magić Zvonko; Anđelković Zoran; Kocev Nikola (Vojnosanitetski Pregled)
Background/Aim. Diabetic nephropathy (DN) is a clinical syndrome characterized by persistent albuminuria, increasing arterial blood pressure and progressive decline in glomerular filtration rate (GFR). When persistent albuminuria is established, antihypertensive treatment becomes most important factor in slowing the progression of diabetic glomerulopathy. The aim of this study was to examine if renoprotective response to a short-term losartan therapy depends on 1166 A/C gene polymorphism for its target receptor. Method. The study included 35 patients with diabetes mellitus type 1 and persistently high urinary albumin excretion rate (UAE: > 30 mg/24 h), genotyped for the 1166 A/C gene polymorphism for the angiotensin II type 1 receptor (AT1R). The participants were segregated into 3 genotype groups according to combinations of A or C allele: AA(16%), AC(15%) and CC(11%). The patients received losartan 50 mg daily for 4 weeks, following 100 mg daily for another 8 weeks. At baseline and after 12 weeks of the treatment period UAE, blood pressure, GFR and filtration fraction (FF) were determined. Results. After 12 weeks of the treatment with losartan, albuminuria was reduced from baseline by 9% [95% confidence interval (CI): 1-17, p = 0.039] in the AA genotype, and by 11% (95% CI: 6-17, p = 0.0001) in the AC genotype. Losartan treatment reduced albuminuria in the CC group by 5% (95%CI: -13-22, p = 0.47). Glomerular filtration rate remained unchanged in all genotype groups. Filtration fraction was significantly reduced from baseline by 0.018 ± 0.024 (p = 0.012) only in the AC genotype. In the AA genotype, FF was reduced from baseline by 0.017 ± 0.03 (p = 0.052), and in the CC genotype by 0.01 ± 0.008 (p = 0.092). In the AA group, systolic blood pressure declined from 136 ± 24 mmHg at baseline, to an average of 121 ± 18 mmHg at the end of the study (p = 0.001). The AC group achived reduction from 131 ± 10 mmHg at baseline to 115 ± 7 mmHg (p = 0.001) during the investigation period. In the AA genotype group losartan reduced diastolic blood pressure from 86 ± 13 mmHg at baseline to 78 ± 8 mmHg (p = 0.004), and in the AC genotype from 88 ± 5 mmHg at baseline to 11.7 ± 5.6 mmHg during the investigation period (p = 0.001). In the CC genotype diastolic blood pressure reduction remained nonsignificant (p = 0.066). Conclusion. The results of our small sample size study provide the evidence that 1166 A/C AT1R polymorphism could be associated with the renoprotective response to losartan therapy.